Acinetobacter species meningitis in children: a case series from Karachi, Pakistan - Saleem, Ali Faisal; Shah, Muhammad Shafaat; Shaikh, Abdul Sattar; Mir, Fatima; Zaidi, Anita K M (The Journal of Infection in Developing Countries, 2011)
Introduction: Multidrug-resistant strains of Acinetobacter pose a serious therapeutic dilemma in hospital practice, particularly when they cause meningitis, as the few antimicrobial agents to which these isolates are susceptible have poor central nervous system (CNS) penetration. Methodology: We retrospectively reviewed the clinical course and outcome of eight consecutive cases of meningitis due to Acinetobacter spp. in children ages 15 years or less, seen in a tertiary care medical center in Karachi, Pakistan. Results: Of the eight cases of Acinetobacter meningitis, isolates from five patients were pan-resistant, and two were multidrug-resistant. A neurosurgical procedure was performed in five of eight patients followed by external ventricular drain insertion prior to the development of infection. Seven received intravenous (IV) polymyxin (mean; 12.8 days), while 5/8 also received intrathecal (IT) polymyxin (mean; 12.0 days). The mean length of hospitalization was 38.7 ± 19 days. All patients achieved cerebrospinal fluid (CSF) culture negativity by the end of treatment (mean; 5.4 days). Two patients died: one with pan-resistant Acinetobacter, and the second with a multi-drug resistant isolate. Conclusion: Post-neurosurgical multidrug-resistant and pan-resistant Acinetobacter meningitis can be successfully treated if appropriate antimicrobial therapy is instituted early. The role of IT polymyxin B administration alone versus combination therapy (IV and IT) needs further study.